PENGEMBANGAN BAHAN AJAR FISIKA BERBASIS KONTEKSTUAL DENGAN MENGINTEGRASIKAN KEARIFAN LOKAL UNTUK MENINGKATKAN PEMAHAMAN KONSEP FISIKA PADA MAHASISWA - Satriawan, Muhammad; Rosmiati, Rosmiati (Universitas Negeri Surabaya, 2016)
This research is a development research that develops teaching materials physics based contextual by integrating local wisdom. To further this research as the basis for the development of textbook physics of high economic value. This study intends to improve the mastery of concepts of physics students. Teaching materials developed using models of R & D with develop model used is a model development Borg & Gall (1985) and Kemp and Dayton (1985), which consists of; (1) research and data collection through surveys, (2) planning, (3) the preparation of teaching materials printed in the form of student worksheets, (4) test the validity of the expert, (5) product revision, (6) field trials small scale, (7) the revised product, (8) broad-scale field trials, (9) the revision of the final product, and (10) the dissemination and implementation. The trials conducted teaching materials student of physics education by test model one group pretest-posttes design. And based on the analysis of the data validation and testing that the teaching materials developed showing the criteria of